Multicenter analysis of treatment outcomes for systemic therapy in well differentiated grade 3 neuroendocrine tumors (NET G3) - Apostolidis, Leonidas; Dal Buono, Arianna; Merola, Elettra; Jann, Henning; Jäger, Dirk; Wiedenmann, Bertram; Winkler, Eva C.; Pavel, Marianne (Cancers, 2021)
Well-differentiated grade 3 neuroendocrine tumors (NET G3) have been distinguished from poorly differentiated neuroendocrine carcinomas (NEC) in the most current WHO classifications. Commonly applied first-line chemotherapy protocols with cisplatin or carboplatin in combination with etoposide (PE) are less effective in NET G3 than NEC. Suggested alternative treatment protocols have not been studied in first-line therapy of NET G3 so far. We performed a retrospective analysis of patients with NET G3 in the databases of 3 German cancer centers. Out of 142 patients, 136 patients received palliative first-line therapy: overall response rate (ORR) was 35.1% for PE (n = 37), 56.4% for FOLFOX (n = 39), 27.3% for temozolomide/capecitabine (TEM/CAP) (n = 22), 45.0% for streptozotocin/5-fluorouracil (STZ/5-FU) (n = 20), and 16.7% for other (n = 18). Median progression-free survival (PFS) for PE was 6.9 months. Compared to PE, PFS in the other treatment groups was 6.9 months for FOLFOX (p = 0.333), 12.0 months for TEM/CAP (p = 0.093), 4.8 months for STZ/5-FU (p = 0.919), and 14.1 months for other (p = 0.014). In a univariate setting, all non-PE patients combined showed a significantly prolonged PFS vs. PE (9.0 months; p = 0.049) which could not be confirmed in a multivariate analysis. In conclusion, NET G3 with FOLFOX showed the highest ORR, and with TEM/CAP showed the longest PFS. Further prospective evaluation of the optimal therapeutic strategy for this tumor entity is needed.
Gesehen am 14.06.2021